An inventory model for deteriorating items with time and price dependent demand and shortages under the effect of inflation. (24th April 2019) - Saha, Sumit; Sen, Nabendu
Variation of demand with time and price is one of the major concerns in any inventory system. Several studies report situations where demand varies with time and price separately. A few researchers have considered the joint effect of demand with price and time on optimal solutions. Thus, a suitable inventory policy in this regard is always sought for. This paper presents an inventory model with selling price and time dependent demand, constant holding cost and time dependent deterioration. In this model, shortages are assumed to be partially backlogged. It is designed keeping in mind to optimise total inventory cost under the effect of inflation. For the solution of the model, an algorithm is proposed and illustrated with numerical values of system parameters. The optimal results are also presented graphically. Finally, sensitivity analysis is performed for different parametric values of system parameters.